Photoregulated plasmon enhanced controllable hydrogen sulfide delivery for photothermal augmented gas therapy. (March 2022) - He, Yaling; Younis, Muhammad Rizwan; Jiang, Chao; He, Gang; He, Jin; Zhang, Yinling; Liu, Hengke; Huang, Peng; Lin, Jing
Highlights: The ammonium sulfide-loaded gold nanovesicles (GV-(NH4 )2 S) were prepared. The GV-(NH4 )2 S exhibited strong near-infrared absorption and high loading capacity of (NH4 )2 S. Upon laser irradiation, GV-(NH4 )2 S enabled the decomposition of (NH4 )2 S to trigger the controllable generation of H2 S . The GV-(NH4 )2 S can be used for multimodal imaging guided photothermal augmented gas therapy. Abstract: Gas therapy has emerged as a promising "green" treatment modality for malignant cancer, however, the targeted delivery of gas donors as well as the controlled gas release remain a formidable challenge. Herein, self-assembled gold nanovesicles (GVs) loaded with ammonium sulfide ((NH4 )2 S) (denoted as GV-(NH4 )2 S) were developed as theranostic nanoplatform for near-infrared (NIR)-activated in-situ hydrogen sulfide (H2 S) generation, controllable gas delivery, and combined photothermal/gas therapy of cancer. GVs had the following features, (1) large hollow cavity, offering high encapsulation efficiency of (NH4 )2 S (∼95%), (2) strong plasmon coupling effect, promoting high photothermal effect under NIR laser irradiation. Upon laser irradiation, GVs were ruptured, thus allowing the simultaneous release and decomposition of (NH4 )2 S to generate H2 S. The generated H2 S induced significant mitochondrial damage and thus reduced adenosine triphosphate (ATP) energy level. Consequently, upon integration, GV-(NH4 )2 S triggered substantial tumor cell killing in vitro and complete 4T1 tumor ablation in vivo, with negligible tumor recurrence and systemic side effects, under the guidance of photoacoustic (PA)/photothermal duplex imaging. This work highlighted the great promise of GVs as a versatile nanocarrier for spatio-temporally controlled and on-demand delivery of gaseous messengers to achieve precision cancer theranostics. Graphical abstract: The ammonium sulfide-loaded gold vesicles (GV-(NH4 )2 S) were developed to achieve controllable H2 S generation in situ and release under near-infrared light stimulus for duplex photothermal/photoacoustic imaging-guided synergistic photothermal/gas therapy. Image, graphical abstract